FITCH IBCA: Argentine Electric Dist. Overview published by Fitch IBCA (M2 Presswire, 2000)
According to Ana Paula Ares, a Director in Fitch IBCA's Buenos Aires office, the sector is not entirely free from risk. 'Distributors are subject to penalties for excessive outages, and the case of Edesur in 1999 illustrates that the financial penalties can be very high,' said Ms. Ares. Furthermore, the first tariff revisions after the restructuring and privatization will take place in 2002. 'There is no experience concerning the revision of tariffs established in the electricity concessions. However, tariff reviews in the gas and electric transmission sector enable us to infer that the regulators are likely to be fair but not overly generous,' said Dolores Teran, also a Director at Fitch IBCA Buenos Aires.